Participation rate of cancer patients in treatment decisions: a cross sectional study - Mohammad Khammarnia; Monireh Eskandari; Arezo Alinezhade Ranjbar; Alireza Ansari-Moghadam; Mostafa Peyvand (Mashhad University of Medical Sciences, 2017)
Background and objective: Cancer is one of the most common diseases and the second reason of death in Iran. Giving decision making authority to patients is one of the fundamental principles of the protection of patients. Patients have rights as consumers of health care services that nurses, physician and other health professionals are responsible for maintaining and protecting it. This study aimed to determine cancer patients’ involvement in treatment decisions making. Methods: This cross-sectional study was carried out as descriptive-analytic with practical purpose in 2017 in Zahedan University of Medical Sciences. The study population included 1,000 patients who had cancer that whom 450 patients were selected by simple random sampling. To measure patient participation in treatment decisions, was used of Levente Kristona standard questionnaire. Reliability and validity of the questionnaire was confirmed (coefficient = 0.82). For data analysis used of software spss21 with descriptive statistics and chi-square tests Results: among the patients, 197 men (53%) and 177 women (47%) with a mean age of 31 years were examined. The results of this study showed that the score of mean participation in treatment decisions among the cancer patients was 30 ± 12 and it was in low level. The patients’ participation in treatment decisions had a significant relationship with education level (P = 0.027), however, it was not statistical significant with gender, age, income, occupation and type of cancer and other demographic variables (P> 0.05). Conclusion: In general, that patients' participation in clinical decision making is weak and low. Since patients’ participation in clinical decisions could affect the quality of treatment decisions, therefore, health care providers should attention more to this fact. Also, culturalizating and education according to patients’ knowledge and use of treatment techniques are recommended for clinical decision making promotion. Paper Type: Research Article